2020
DOI: 10.1111/jors.12506
|View full text |Cite
|
Sign up to set email alerts
|

What do divided cities have in common? An international comparison of income segregation

Abstract: This paper provides a comparative assessment of income segregation within cities in 12 countries. We use spatial entropy indexes based on small-scale gridded income data and consistent definition of city boundaries to ensure international comparability of our segregation measures. Results show considerable variation in the levels of income segregation across cities, even within countries, reflecting the diversity of cities within urban systems. Larger, more affluent, productive, and more unequal cities tend to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
(50 reference statements)
2
2
0
Order By: Relevance
“…First, we observe that both intensity and separation levels associate with municipality size, income inequality, and migrant share. While this result is in line with past research (Gordon & Monastiriotis, 2006;Natale et al, 2018;Veneri et al, 2021), it also suggests that the association of segregation with city size, migrant share, and income inequality are three faces of the same phenomenon. These three variables are correlated in the Netherlands, and all of which are similarly and positively associated with segregation intensity (linear relation) and separation (concave relation).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…First, we observe that both intensity and separation levels associate with municipality size, income inequality, and migrant share. While this result is in line with past research (Gordon & Monastiriotis, 2006;Natale et al, 2018;Veneri et al, 2021), it also suggests that the association of segregation with city size, migrant share, and income inequality are three faces of the same phenomenon. These three variables are correlated in the Netherlands, and all of which are similarly and positively associated with segregation intensity (linear relation) and separation (concave relation).…”
Section: Discussionsupporting
confidence: 92%
“…The share of individuals with a non-Western migration background ranges from 1 to 38% of the municipality population, with a median of 5%. Finally, Dutch municipalities show relatively low income inequality compared to the rest of OECD countries (Veneri et al, 2021).…”
Section: Datasetsmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, 3D factors affect housing selections, even in the 2D aspect, when buyers are not self-aware. We also found that different age cohorts have different demands for 2D locational factors, a fact that is proven by existing literature [21,22,61]. Younger adults love entertainment facilities, while the middle-aged group emphasizes access to premium educational resources and sports facilities.…”
Section: Discussionsupporting
confidence: 70%